Lymph nodes metastasis of gastric cancer: Measurement with multidetector CT oblique multiplanar reformation—correlation with histopathologic results. Issue 39 (September 2016) - Wang, Zhi-Long; Zhang, Xiao-Peng; Tang, Lei; Li, Xiao-Ting; Wu, Ying; Sun, Ying-Shi
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of this study was to retrospectively evaluate the ability of multidetector computed tomography (MDCT) oblique multiplanar reformation (MPR) for differentiating metastatic lymph nodes (LNs) in patients with gastric cancer. Seventy-nine patients with gastric cancer underwent preoperative computed tomography (CT). One-to-one correlation of LN was made between CT oblique multiplanar reformation and histopathologic slides. Long diameters, short diameters, and short-to-long axis ratios of LNs were evaluated to differentiate metastasis. Short diameters of nodes performed better for diagnosing metastasis than long diameters and short-to-long ratios. Sensitivity, specificity, accuracy, and area under the receiver operating characteristic curve of short diameter were 57.8%, 74.7%, 68.2%, and 0.713, respectively. With different thresholds of short diameters of nodes (No. 8 group >6 mm and other groups >4 mm), total sensitivity, specificity, and accuracy can reach 57.2%, 79.0%, and 70.3%, respectively. MDCT oblique MPR images have certain reference value to distinguish metastasis of LNs in gastric cancer. The diagnostic power for LN metastasis of gastric cancer can be improved by using different threshold for No. 8 group LNs and other groups.